2020
DOI: 10.3390/nu12020402
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Glutamine Levels in Relation to Intensive Care Unit Patient Outcome

Abstract: Low and high plasma glutamine levels are associated with increased mortality. This study aimed to measure glutamine levels in critically ill patients admitted to the intensive care unit (ICU), correlate the glutamine values with clinical outcomes, and identify proxy indicators of abnormal glutamine levels. Patients were enrolled from three ICUs in South Africa, provided they met the inclusion criteria. Clinical and biochemical data were collected. Plasma glutamine was categorized as low (<420 µmol/L), normal (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
1
13
1
1
Order By: Relevance
“…This finding is supported by the literature, as low Gln concentrations upon admission to the ICU have previously been reported to be correlated with mortality 35 37 . In this study, in contrast to the study of Blauuw et al 38 , only the serum (but not the urine) Gln concentration was significantly higher in non-survivors compared to survivors. Interestingly, the incidence of septic shock was not associated with changes in either the urine or serum concentrations of Gln.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding is supported by the literature, as low Gln concentrations upon admission to the ICU have previously been reported to be correlated with mortality 35 37 . In this study, in contrast to the study of Blauuw et al 38 , only the serum (but not the urine) Gln concentration was significantly higher in non-survivors compared to survivors. Interestingly, the incidence of septic shock was not associated with changes in either the urine or serum concentrations of Gln.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, the incidence of septic shock was not associated with changes in either the urine or serum concentrations of Gln. Blaauw et al 38 stated that both low and high values of the serum Gln concentration are associated with increased mortality, as changes in the Gln concentration may be U-shaped. Likewise, according to Tsujimoto et al 39 , both lower and higher values of the serum Gln concentration were reported to be associated with a risk of mortality among patients with sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed a similar mortality and length of ICU stay in both polytrauma groups. However, contradictory findings have been recently reported in the literature regarding the linking between low or high GLN levels and mortality, so the debate is still open (22).…”
Section: Discussionmentioning
confidence: 99%
“…The low glutamine associated with a high mortality may just be a biomarker without any mechanistic connection. Only a few publications include hyperglutaminemic ICU patients [ 9 11 , 14 16 ]. A higher than normal plasma glutamine concentration is also reported to be associated with unfavourable outcomes, both at admission and during the course of critical illness [ 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%